2006
DOI: 10.1177/153537020623100506
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Fas and Fas-Related Molecules in Patients with Silicosis

Abstract: Persons with silicosis have not only respiratory disorders but also autoimmune diseases. To clarify the mechanisms involved in the dysregulation of autoimmunity found in patients with silicosis, we have been focusing on Fas and Fas-related molecules in the Fas-mediated apoptotic pathway, because Fas is one of the most important molecules regulating auto-immunity involving T cells. Our findings showed that patients with silicosis exhibited elevated serum soluble Fas levels, an increased relative expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 76 publications
(65 reference statements)
2
50
0
Order By: Relevance
“…The radiological features consist in multiple well-defined round opacities, measured between 0.5 and 5 cm in diameter, distributed throughout both lung fields but predominantly at the periphery [8]. The association between long exposure to silica, pneumoconiosis and RA is proved [9]. In the study of Calvert GM et al [10], the link between crystalline silica exposure and RA is well demonstrated.…”
Section: Discussionmentioning
confidence: 78%
“…The radiological features consist in multiple well-defined round opacities, measured between 0.5 and 5 cm in diameter, distributed throughout both lung fields but predominantly at the periphery [8]. The association between long exposure to silica, pneumoconiosis and RA is proved [9]. In the study of Calvert GM et al [10], the link between crystalline silica exposure and RA is well demonstrated.…”
Section: Discussionmentioning
confidence: 78%
“…Consequently, it is speculated that there is a particular fraction of CD4+ T lymphocytes in SILs that expresses weak levels of membrane Fas, secretes higher levels of soluble Fas, DcR3, and spliced variants, and is resistant to anti-Fas autoantibody-induced apoptosis, as shown in Fig. 1 and previous reports (30,43,44). Because the patients with a weaker MFI of membrane Fas have a higher titer of anti-nuclear antigens (ANA), as reported previously (30), selfrecognizing clones in SILs may be included in this fraction, because these clones may survive longer and show resistance to apoptosis.…”
Section: Alterations Of Fas-related Molecules and Cd4+25+ Regulatory mentioning
confidence: 85%
“…1 and preliminarily reported previously (30,43,44). The findings of the levels of factors in extracellular spaces, such as soluble Fas, DcR3, and products from various alternatively spliced fas variants indicate that apoptosis mediated by membrane Fas seems to interfere with these molecules and Fas-mediated apoptosis is reduced.…”
Section: Alterations Of Fas-related Molecules and Cd4+25+ Regulatory mentioning
confidence: 99%
See 1 more Smart Citation
“…They developed a syndrome that is serologically and pathologically similar to human SLE. In humans, the serum levels of soluble Fas (sFas), the most typical alternatively spliced variant of wild-type fas genes, are higher in silicosis and SLE patients (17,18 (17). (20,21 (22,24,25 Fig.…”
Section: F I G U R E 3 S T a I N I N G O F T H E G L O Me R U L U Smentioning
confidence: 99%